Apomeiosis stability in weeping lovegrass: genetic control across time and environments - Quevedo, Martín Raúl (2025)
Weeping lovegrass (Eragrostis curvula) is a perennial grass that exhibits a specific form of embryo sac development known as Eragrostis-type, that is being used as a model species to investigate the genetic and epigenetic regulation of apomixis. Most apomictic plants are facultative, with sexuality typically strongly repressed or expressed at very low levels under normal conditions. Stressful situations can de-repress sexuality, increasing the occurrence of sexual processes in apomictic plants. In E. curvula, mapping studies have shown that apomeiosis is controlled by a single genomic region. However, the frequency of apomictic reproduction varies widely among hybrids(from 3% to 97%), suggesting that additional regulatory mechanisms may be involved. This study aimed to evaluate the stability of apomeiosis expression in sibling plants exhibiting differentfrequencies of apomeiosis, assessed across multiple years and contrasting environmental conditions. Plants from a mapping population derived from a cross between the tetraploid cultivars OTA-S and Don Walter were analyzed. Panicles were collected at the onset of anthesis for phenotypic analysis based on the identification of structures characteristic of either apomictic or sexual development. Samples from plants growing in the greenhouse and also under field conditions collected during spring flowering periods (November-December) for at least three years were evaluated. Eleven plants were selected to be evaluated based on their apomeiosisfrequency: low (≤ 30%), medium (30–70%), or high (≥ 70%). Results showed that all the evaluated plants maintained consistent levels of apomeiosis expression across the years. The same situation was observed between samples grown under greenhouse or field conditions. These findings suggest that, while environmental factors may influence the expression of the trait, genetic factors play a more dominant role in regulating apomeiosis in E. curvula.